Pengaruh Locus of Control dan Experience Regret Terhadap Keputusan Investasi Mahasiswa Manajemen Angkatan 2018 Universitas Islam Bandung - Nadira Rizky Ridiananda; Lasmanah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The changing times make people look for ways to maintain an asset they have, ranging from ordinary savings to investments in goods and letters. Now people want to maintain assets that can increase every year, unlike ordinary savings whose amount is always fixed, so they make an investment that has many types and easy ways. As data revealed by the Indonesia Stock Exchange (IDX), the number of investors every year increases in terms of capital market investors until January 21, 2022, the number of investors increases by 7.75 investors, which means an increase of 260 thousand from December 2021. From this composition, there are 81% of the millennial generation. dominating. This research aims to find out whether or not there is an influence of Locus of Control and Experience Regret on the Investment Decisions of Management Students at the Islamic University of Bandung Batch 2018 consisting of 75 respondents. Data collection was carried out by distributing online questionnaires to Management students at the Bandung Islamic University Class of 2018. Then the data was processed in the SPSS for windows application version 26.00. The results of the study show that Locus of Control (X1) has an effect on Investment Decisions (Y) and Experience Regret (X2) has no effect on Investment Decisions (Y) for Management students at the Islamic University of Bandung, Class of 2018. Abstrak. Perkembangan zaman yang terus berubah membuat manusia mencari cara bagaimana mempertahankan suatu asset yang dimiliki, mulai dari tabungan biasa hingga investasi dalam bentuk barang dan surat. Sekarang manusia ingin mempertahankan asset yang setiap tahunnya dapat bertambah,tidak seperti tabungan biasa yang jumlahnya selalu tetap, sehingga mereka melakukan sebuah investasi yang memiliki banyak jenis dan cara yang mudah. Seperti data yang diungkapkan Bursa Efek Indonesia (BEI), jumlah investor setiap tahunnya meningkat dari sisi investor pasar modal hingga 21 Januari 2022 jumlah investor meningkat sebesar 7,75 investor yang berarti bertambah 260 ribu dari Desember 2021. Dari komposisi tersebut terdapat 81% Generasi millennial dan Gen Z yang mendominasi. Penelitian kali ini penulis memiliki tujuan ingin mengetahui ada atau tidak pengaruh Locus of Control dan Experience Regret terhadap Keputusan Investasi Mahasiswa Manajemen Angkatan 2018 Universitas Islam Bandung yang terdiri dari 75 responden. Pengumpulan data dilakukan dengan cara menyebarkan kuisioner secara online kepada mahasiswa Manajemen Universitas Islam Bandung Angkatan 2018. Kemudian data tersebut diolah pada aplikasi SPSS for windows versi 26.00. Hasil dari penelitian menunjukkan bahwa Locus of Control (X1) berpengaruh terhadap Keputusan Investasi (Y) dan Experience Regret (X2) tidak berpengaruh terhadap Keputusan Investasi (Y) mahasiswa Manajemen Universitas Islam Bandung Angkatan 2018.